2015
DOI: 10.1016/j.lithos.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

A radiogenic isotopic (He-Sr-Nd-Pb-Os) study of lavas from the Pitcairn hotspot: Implications for the origin of EM-1 (enriched mantle 1)

Abstract: We present new He-Sr-Nd-Pb-Os isotopic compositions and major and trace-element concentrations for ten subaerially-erupted lavas and one seamount lava associated with the Pitcairn hotspot. The most geochemicallyenriched lavas at the Pitcairn hotspot have signatures that are consistent with recycled sediments derived from upper continental crust. Pitcairn lavas have elevated Ti, which also supports the presence of a mafic protolith in the Pitcairn mantle. A subset of Pitcairn seamount samples, including the sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 86 publications
2
21
0
Order By: Relevance
“…Hart et al (1992) argue that FOZO could represent a rather primitive mantle source with undifferentiated trace element content and elevated 3 He/ 4 He ratios. Very recently, Garapić et al (2015) also concluded that the same FOZO reservoir with high 3 He/ 4 He was sampled in few Pitcairn samples with 206 Pb/ 204 Pb ratios > 18, while unpublished He results mentioned in Class and Goldstein (2005) also suggest the presence of high 3 He/ 4 He ratios in Gambier lavas with 206 Pb/ 204 Pb ratios > 18. It could therefore be concluded that the FOZO component interpreted as being an undegassed primitive mantle (Hart et al, 1992;Hauri et al, 1994;Jackson and Jellinek, 2013), is the peridotitic component of our petrological/geochemical model.…”
Section: Gambier Fozo and The 'Railway Crossing'mentioning
confidence: 96%
“…Hart et al (1992) argue that FOZO could represent a rather primitive mantle source with undifferentiated trace element content and elevated 3 He/ 4 He ratios. Very recently, Garapić et al (2015) also concluded that the same FOZO reservoir with high 3 He/ 4 He was sampled in few Pitcairn samples with 206 Pb/ 204 Pb ratios > 18, while unpublished He results mentioned in Class and Goldstein (2005) also suggest the presence of high 3 He/ 4 He ratios in Gambier lavas with 206 Pb/ 204 Pb ratios > 18. It could therefore be concluded that the FOZO component interpreted as being an undegassed primitive mantle (Hart et al, 1992;Hauri et al, 1994;Jackson and Jellinek, 2013), is the peridotitic component of our petrological/geochemical model.…”
Section: Gambier Fozo and The 'Railway Crossing'mentioning
confidence: 96%
“…To solve the 3rd Pb paradox in MORB, the constancy of ratios indicated by Eqs. (1) to (6) is examined first using the mean trace element contents of ocean floor basalts (OFB-Jenner and O'Neill, 2012) and Stracke (2006, 2010) and Garapic et al (2015); DMM composition is from average concentrations ± largest spread from the ranges of Workman and Hart (2005)-all in ppm. Element ratios ±2 sigma uncertainties in sub-columns m1 and m1′ were calculated from mean values of individual elements.…”
Section: Constancy Of Ratios and 3rd Pb Paradox In Morbmentioning
confidence: 99%
“…The enriched component is compositionally akin to OIB as they share a common source. The slopes of the binary mixing lines (L1-L1′, L2-L2′ and L3) were respectively determined in three ways: (m1-m1′) ratios of mean values of individual elements ±2 sigma uncertainties in the two datasets, (m2-m2′) linear regression of individual element pairs ± least-square uncertainties and (m3) through mixing between DMM (Workman and Hart, 2005) and an enriched OIB component derived from the mean concentrations of the isotopically most extreme OIB from HIMU, EM1 and EM2 type localities Stracke, 2006, 2010) and most recent data for Pitcairn (Garapic et al, 2015) ±2 sigma uncertainties. As Stracke (2006, 2010) have proposed, the parental magmas for this OIB component originate mainly (ca.…”
Section: Constancy Of Ratios and 1st And 2nd Pb Paradoxes In Morbmentioning
confidence: 99%
“…These isotopic end‐members have been linked to different lithospheric materials (oceanic crust, oceanic mantle lithosphere, and sediments) subducted into the mantle in the geologic past, which are returned (“recycled”) to the shallow mantle and melted beneath oceanic hotspot volcanoes and erupted as OIBs [ Cohen and O'Nions , ; Hofmann and White , ; White and Hofmann , ]. For example, subducted upper continental crust is suggested to give rise to the EM2 mantle end‐member [ White and Hofmann , ; Jackson et al ., ; Workman et al ., ], but the origin of EM1 is not as well understood [ Weaver , ; Eiler et al ., ; Gasperini et al ., ; Eisele et al ., ; Honda and Woodhead , ; Geldmacher et al ., ; Salters and Sachi‐Kocher , ; Collerson et al ., ; Hart , ; Konter and Becker , ; Garapic et al ., ]. The HIMU mantle end‐member is characterized by the most radiogenic Pb‐isotopic compositions in the oceanic mantle, and is thought to originate from recycling of ancient subducted oceanic crust [e.g., Chase , ; Hofmann and White , ; Zindler et al ., ; Nakamura and Tatsumoto , ; Dupuy et al ., ; Graham et al ., ; Hauri and Hart , ; Hémond et al ., ; Roy‐Barman and Allègre , ; Woodhead , ; Hanyu and Kaneoka , ; Kogiso et al ., ; Salters and White , ; Schiano et al ., ; Lassiter et al ., ; Stracke et al ., ; Stroncik and Haase , ; Kelley et al ., ; Nishio et al ., ; Chan et al ., ; Parai et al ., ; Day et al ., ; John et al ., ; Hanyu et al ., ; Kawabata et al ., ; Salters et al ., ; Krienitz et al ., ; Cabral et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…These isotopic end-members have been linked to different lithospheric materials (oceanic crust, oceanic mantle lithosphere, and sediments) subducted into the mantle in the geologic past, which are returned (''recycled'') to the shallow mantle and melted beneath oceanic hotspot volcanoes and erupted as OIBs [Cohen and O'Nions, 1982;Hofmann and White, 1982;White and Hofmann, 1982]. For example, subducted upper continental crust is suggested to give rise to the EM2 mantle end-member Jackson et al, 2007;Workman et al, 2008], but the origin of EM1 is not as well understood [Weaver, 1991;Eiler et al, 1995;Gasperini et al, 2000;Eisele et al, 2002;Honda and Woodhead, 2005;Geldmacher et al, 2008;Salters and Sachi-Kocher, 2010;Collerson et al, 2010;Hart, 2011;Konter and Becker, 2012;Garapic et al, 2015]. The HIMU mantle end-member is characterized by the Key Points:…”
Section: Introductionmentioning
confidence: 99%